The Level of Utilizing Artificial Intelligence Applications by Arabic Language Teachers in Secondary Education (Journal of the College of Basic Education, 2026)
The current research aims to identify "the level of utilizing artificial intelligence applications by Arabic language teachers in secondary education," by answering the following questions:What is the level of utilizing artificial intelligence applications by Arabic language teachers in secondary education?What is the level of utilizing artificial intelligence applications by Arabic language teachers in secondary education according to the gender variable?What is the level of utilizing artificial intelligence applications by Arabic language teachers in secondary education according to the variable of years of experience?To achieve the research objective, the researchers employed the descriptive survey method. The research population consisted of (637) Arabic language teachers in the Directorate of Education in Diyala Governorate for the academic year (2025-2026). The researchers developed the research instrument, a questionnaire, which in its final form comprised (31) items. This was conducted after presenting it to a panel of experts in the fields of Arabic language teaching methods, artificial intelligence, and measurement and evaluation. The researchers utilized a five-point Likert scale to provide response alternatives for each item. To verify validity (both face validity and construct validity), the instrument achieved an acceptance criterion of (80%). Its reliability was also confirmed, rendering it ready for final application.